Examine The Relationship Of SCM Practices And Organizational Behaviour : A Case Analysis Of Malaysia Service Industry - Khang, Tai Siaw (2009)
The purpose of this study is to investigate the six dimensions in supply chain management (SCM), which includes: Leardership, Knowledge Sharing, Information System Adoption, Training and Customer Oriented.